Visual Servoing via Advanced Numerical Methods - Chesi, Graziano; Hashimoto, Koichi; SpringerLink (Online service) (London : Springer London, 2010)
The text of Visual Servoing via Advanced Numerical Methods has its roots in an invited session presented at the IEEE International Conference on Robotics and Automation at Kobe in May 2009. The work presented here has been much expanded and gives a comprehensive overview of the state of the art in this important area of robotics. The latest contributions from well-known experts in visual servoing provide the reader with solutions to the fundamental and specific problems that have to be solved in using camera-derived feedback to control robotic motion and make it imitative of the actions of human beings. These solutions are based on dedicated numerical methods the development of which has been facilitated by recent progress in video devices, computer hardware and optimisation techniques. The book is organised into three parts reflecting: the uses of image processing and computer vision; control, optimal and robust control; and stability, performance and robustness analysis in visual servoing.
Vision -- Catadioptric Stereo with Planar Mirrors: Multiple-view Geometry and Camera Localization -- Empirical Characterization of Convergence Properties for Kernel-based Visual Servoing -- High-speed Visual Feedback Control for Grasping and Manipulation -- Human-machine Cooperative Manipulation with Vision-based Motion Constraints -- Luminance: A New Visual Feature for Visual Servoing -- Visual Servoing for Beating Heart Surgery -- Estimation and Path-Planning -- A Variational Approach to Trajectory Planning in Visual Servoing -- Estimation of Homography Dynamics on the Special Linear Group -- Image Measurement Errors in Visual Servoing: Estimating the Induced Positioning Error -- Multicriteria Analysis of Visual Servos through Rational Systems, Biquadratic Lyapunov Functions, and LMIs -- Path-Planning for Visual Servoing: A Review and Issues -- Single Camera Structure and Motion Estimation -- Visual Servoing and Pose Estimation with Cameras Obeying the Unified Model -- Control -- Gradient Projection Methods for Constrained Image-based Visual Servo -- Image-based Visual Servo Control Design with Multi-Constraint Satisfaction -- Points-based Visual Servoing with Central Cameras -- Sensor-based Trajectory Deformation: Application to Reactive Navigation of Nonholonomic Robots -- Unicycle-like Robots with Eye-in-Hand Monocular Cameras: From PBVS towards IBVS -- Unmanned Helicopter Control via Visual Servoing with Occlusion Handling -- Visual Servoing via Nonlinear Predictive Control.
Keywords: Engineering; Computer vision; Biomedical engineering; Engineering; Control; Image Processing and Computer Vision; Signal, Image and Speech Processing; Biomedical Engineering